2018
DOI: 10.1037/pha0000207
|View full text |Cite
|
Sign up to set email alerts
|

Differences in puff topography, toxicant exposure, and subjective response between waterpipe tobacco smoking men and women.

Abstract: Waterpipe tobacco smoking (WTS) exposes users to toxicants in much greater amounts than a cigarette. Little is known about how gender affects WTS toxicant exposure and subjective response. Data from three WTS clinical laboratory studies were combined for analysis. Participants ( = 99; 38 women) completed a 45-min WTS session where they smoked a waterpipe ad libitum. Puff topography was measured throughout, and plasma nicotine concentration, expired air carbon monoxide (CO), and subjective responses were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Similarly, studies have reported that Cg smoking in the boys is more intense and frequent than girls, which, once again, would mean greater smoke consumption [60]. In a recent study from United States, toxicant exposure to Wp smoke was greater in men than women with men inhaling a greater smoke volume and higher plasma nicotine concentrations after smoking [61]. This greater smoke consumption indicates that the boys are more exposed to smoke toxicants, thus may be more affected.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have reported that Cg smoking in the boys is more intense and frequent than girls, which, once again, would mean greater smoke consumption [60]. In a recent study from United States, toxicant exposure to Wp smoke was greater in men than women with men inhaling a greater smoke volume and higher plasma nicotine concentrations after smoking [61]. This greater smoke consumption indicates that the boys are more exposed to smoke toxicants, thus may be more affected.…”
Section: Discussionmentioning
confidence: 99%
“…The observed differential modulation of ferritin level by smoking according to gender could be due to a combination of behavioral and physiological factors. For example, one study showed greater total puff volume and blood nicotine levels in men during Wp smoking [ 34 ]. In addition, gender differences in nicotine metabolism have been reported, which could suggest that girls might have the urge to smoke more often and more intensely to maintain sufficient circulatory nicotine via smoking Cg more often compared to Wp [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the cigarette and incense scenarios, the concentrations increased continuously until the end of smoking or burning, but during shisha smoking, the concentrations varied as a result of the puffing sequence or the addition of charcoal. The pollution emitted during smoking depends on the puffing and smoking behaviour [144][145][146]. The emission factor is also dependent on the shisha setup (bowel size, head size, hose length, etc.)…”
Section: Temporal Variation Size Distirbutions and Particle Lossesmentioning
confidence: 99%